PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 008 TELUK MEGA KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Zaini Zaini; Munjiatun Munjiatun; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study in the background backs by low yields social studies class student V SDN 008 Teluk Mega bay with an average grade 67.4%. While the value of minimum criteria for completeness (KKM) IPS is 70. Among the students numbering 25 people, only 10 students who reach KKM with classical completeness 40%)%. This study is a Classroom Action Research (CAR) conducted aims to improve learning outcomes IPS fifth grade students of SDN 008 Mega bay with the Application Model of Quantum Teaching To Improve Student Learning Outcomes IPS Class V SDN 008 Mega Gulf "Tanah Putih Rokan Hilir. Formulation of the problem: if the application of Quantum Teaching Model Application To Enhance Student Learning Outcomes IPS Class V SDN 008 Mega Gulf "Tanah Putih Rokan Hilir. This study was carried out on March 18, 2015 until 15 April 2015 to 2 cycles. The subjects were students of class V SDN 008 Mega bay numbering 25 people were used as a source of data. Data collection instruments in this thesis is a sheet activities of teachers and students and learning outcomes. Teacher activity during the learning process by using the application of Quantum Teaching Model in the first cycle with the first meeting 50% Less categories, the first cycle of the second meeting of 58.33% to the category of Self. In the second cycle the first meeting of 70.83% with good category, the second cycle II meeting of 87.50% with a very good category. Increased. Activity of students during the learning process by using the application of Quantum Teaching Model in the first cycle with the first meeting 41.6% Less categories, the first cycle of the second meeting of 54.16% to the category of Self. Increased. In the second cycle the first meeting of 66.66% with good category. In the second cycle II meeting of 83.33% with a Very Good category has increased. Application of Model Quantum Teaching in the learning process can improve student learning outcomes IPS from a base score average (67.4) to an average of UH I (69.6) base score (48.88%) to UH II to the average (75.8) experienced increase.Keywords: Model Quantum Teaching, Learning Outcomes IPS